2014
DOI: 10.1016/j.joca.2014.02.225
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of knee joint biomechanics during free gait and cartilage T2 mapping values in healthy individuals in their twenties and forties

Abstract: Purpose: Gait metric alterations have been reported in patients suffering from chronic ankle instability (CAI). Those studies comprised relatively small cohorts and their findings were inconsistent. This study was undertaken to examine spatiotemporal gait parameters in patients with CAI and examine the relationship between self-reported disease severity and the magnitude of gait abnormalities. Methods: Medical files of all patients diagnosed as having CAI and referred to a private treatment center between May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The gait was evaluated using three-dimensional (3D) gait analysis and the kinetic and kinematic values of the gait were determined using previously reported methods [ 19 ]. The 3D trajectory data, sampled at 100 Hz, were collected using a 10-camera motion analysis system (Motive; Optitrack Japan, Tokyo Japan; Venus 3D; Nobby Tech, Tokyo, Japan) and digitally recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gait was evaluated using three-dimensional (3D) gait analysis and the kinetic and kinematic values of the gait were determined using previously reported methods [ 19 ]. The 3D trajectory data, sampled at 100 Hz, were collected using a 10-camera motion analysis system (Motive; Optitrack Japan, Tokyo Japan; Venus 3D; Nobby Tech, Tokyo, Japan) and digitally recorded.…”
Section: Methodsmentioning
confidence: 99%
“…A four-link model with four segments for the pelvis, thigh, shank (lower leg), and foot was used in the present study, as reported previously [ 19 ]. Global optimization was used to estimate the segments [ 20 ], and the model was customized to each subject using the marker data collected during each individual’s static calibration.…”
Section: Methodsmentioning
confidence: 99%